The Effect Of Perceived Ease Of Use And Trust On Halodoc Customer Satisfaction In Semarang During Pandemic Covid-19 - Mona Tiorina Manurung; Chusnul Zulaika; Ambar Dwi Erawati (Institute of Computer Science (IOCS), 2022)
This study is a quantitative study that aims to see the effect of perceived ease of use and trust on Halodoc customer satisfaction during the Covid-19 pandemic. The sampling technique in this study used a purposive sampling method with the criteria of respondents living in the city of Semarang and having used the Halodoc application at least 1 time. Methods of data collection using a questionnaire with a Likert Scale of 53 respondents. The data from this study were tested using multiple linear regression analysis through the SPSS 16.0 program. The results of this study indicate that perceived ease of use has a significant effect on customer satisfaction and the trust variable also has a significant effect on customer satisfaction. The value of R Square obtained is 0.589. This means that the variable of customer satisfaction is influenced by the perceived ease of use and trust of 58.9%. While the remaining 41.1% is influenced by other variables that are not used in this study.